Incivility Beyond the Classroom Walls - Wendy L. Bjorklund; Diana L. Rehling (Park University, 2011)
Classroom incivility has become a major concern in higher education. Faculty and students frequently interact outside of class, and the lack of civility in those interactions can influence the relationship between students and faculty and impact classroom dynamics. Based on a survey of faculty at a Midwestern public university, this study reports that faculty experience a fair amount of moderately inappropriate student behavior outside the classroom, including missing scheduled appointments, wearing revealing clothing, and requesting a grade change. These results can help faculty and administrators guide students toward more appropriate behavior and create better relationships between faculty and students.